The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.29333/ejgm/82406
|View full text |Cite
|
Sign up to set email alerts
|

Bupropion Hydrochloride Induced Serum Sickness-Like Reaction

Abstract: Sustained-release bupropion is commonly used for the symptomatic relief of depressive disorders and as an adjuvant in smoking cessation therapy. The frequency of adverse reactions with bupropion has been estimated to be more than 1%. Hypersensitivity reactions to bupropion are fairly common and include rare cases of serum sickness-like reaction. Here we report a case of bupropion hydrochloride induced serum sickness-like reaction. Complete resolution of symptoms was achieved on discontinuing bupropion and inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Low-grade inflammation is believed to be involved in the poor responsiveness to regular antidepressants 1 . Moreover, despite the repeatedly mentioned anti-inflammatory effects, some controversies are reported regarding bupropion action including the development of some inflammatory abnormalities such as type 1 hypersensitivity reactions (erythema multiformeis) and serum sickness-like reaction 26,27 . Moreover, Eller et al observed elevated levels of IL-8 in response to bupropion 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Low-grade inflammation is believed to be involved in the poor responsiveness to regular antidepressants 1 . Moreover, despite the repeatedly mentioned anti-inflammatory effects, some controversies are reported regarding bupropion action including the development of some inflammatory abnormalities such as type 1 hypersensitivity reactions (erythema multiformeis) and serum sickness-like reaction 26,27 . Moreover, Eller et al observed elevated levels of IL-8 in response to bupropion 28 .…”
Section: Discussionmentioning
confidence: 99%